Pengungkapan Pemerasan dan Pengancaman pada Alat Bukti Kasus Pinjaman Online (Kajian Linguistik Forensik) - Ali Kusno; M. Bahri Arifin; Widyatmike Gede Mulawarman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aims to identify the content of extortion and threats in messages sent by collectors from PT (reported) to NT (whistleblower). This research uses the descriptive qualitative method. The research data is in the form of the use of language as legal evidence sourced from the statements of police investigators. The data analysis technique uses an interactive model. Data analysis used content analysis with the theory of critical discourse analysis, sociopragmatics, and semiotics of Roland Barthes. The analysis results show that the PT application collector should be suspected of having threatened and blackmailed NT to immediately make loan payments to the PT application even though NT felt that it had fulfilled its obligations. In addition, the unclear lending status is detrimental to NT as a debtor. The collector forced NT to immediately make several payments, accompanied by several consequences for distributing personal data, vulgar photos, and physical threats to NT and her family. The use of threats usually accompanies blackmail.